2013
DOI: 10.1080/15700763.2013.815783
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts of Interest: A Case Study Exploring Constraints on Educational Leaders’ Agency as Representatives of Refugee Interests

Abstract: School-aged children comprise 35-40 percent of the annual influx of new refugees. Yet, refugee parents have limited avenues of political representation until they attain citizenship. As the vanguard of government, schools offer refugee populations opportunities for representation through the agency of the educational leaders. Deploying surrogate representation as a theoretical lens, this case study explored how educational leaders represented the interests of the refugee populations they serve. Findings sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…This finding concurs with previous studies. In the US, Hanna (2013) found that educators at one school separated out newly arrived pupils to study for a high‐stakes English language exam despite knowing that this type of provision was detrimental in the longer term, a case of 'rational agency in conflict with policy incentives' (p. 146). At schools in England, McIntyre and Hall (2018) found that 'the realities of school life' (p. 14) often got in the way of best practice with refugee pupils; a 'policy paradox' required schools to look out for pupil well‐being, on the one hand, while performing on pressurised examinations, on the other.…”
Section: Discussionmentioning
confidence: 99%
“…This finding concurs with previous studies. In the US, Hanna (2013) found that educators at one school separated out newly arrived pupils to study for a high‐stakes English language exam despite knowing that this type of provision was detrimental in the longer term, a case of 'rational agency in conflict with policy incentives' (p. 146). At schools in England, McIntyre and Hall (2018) found that 'the realities of school life' (p. 14) often got in the way of best practice with refugee pupils; a 'policy paradox' required schools to look out for pupil well‐being, on the one hand, while performing on pressurised examinations, on the other.…”
Section: Discussionmentioning
confidence: 99%